A Systematic Literature Review on Suicide: Risk and Protection Factors in Latin American Youth 1995-2017 - González Sancho, Roy David (2020)
Objective. To determine the state of research on protective and risk factors of suicide in young people in several Latin American countries. Method. The study was conducted following a Systematic Literature Review with a qualitative approach. Results. Most studies analyzed for this article have been conducted from within the health sciences with a predominance of quantitative approaches, focusing mainly on risk factors and, to a lesser extent, on protective factors. However, there is a need to study the latter in greater depth, as well as prevention measures that may be useful in future interventions and research. In addition, it has been found that the family, as the first space of social interaction, represents a determining element in the development of both protective and risk factors in young people. Furthermore, for this population, the combination of different risk factors could considerably aggravate the occurrence of a suicide attempt or consummation.